Workshop on Governance & Institutions Across Scales in Climate Resilient Food Systems - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) Flagship 4 organised a workshop in September on "Governance & Institutions Across Scales in Climate Resilient Food Systems" in Brussels, Belgium. The workshop gathered social and political scientists, mixed with food security, water and agriculture experts. Together the diverse group aimed to pan out and highlight where CCAFS new Flagship "Policies and Institutions in Climate Resilient Food Systems", could add value to the field of policies, climate change and food security. The connection institutions and food security is still la relatively unexplored territory in which CCAFS aims to make a difference. Photo: C. Schubert (CCAFS)